Effect of additives and moisture on the fermentation quality and bacterial community of high moisture ear corn - Li, Jiajun; Li, Zheng; Shang, Songlin; Zhao, Xi; Zhang, Wenjing; Zhang, Xinrui; Bai, Jinni; Yang, Zhiye; Guo, Kaijun (Frontiers in Microbiology, 2023)
Maize (Zea mays L) is one of the most widely cultivated crops used as energy feeds. The aim of this study was to evaluate the effects of two lactic acid bacteria additives on the fermentation quality and bacterial community of high moisture ear corn (HMEC) silage at different moisture levels. The study utilized corn kernels and cobs harvested at the stage of complete ripeness as the primary material. The cob was crushed and divided into three treatment groups: an untreated control group (CK), a group treated with a mixture of Lactobacillus plantarum and Lactobacillus brucei (TQ), or a group treated with a mixture of Lactococcus lactis and Lactobacillus brucei (KT). Moisture contents were adjusted to 37.5% (L), 42.5% (M) or 47.5% (H) and then silaged for 180 days. Compared to CK, TQ, and KT elevated the dry matter, crude protein, starch, lactic and acetic acid content of HMEC and reduced the pH, neutral detergent fiber, acid detergent fiber and ammonia nitrogen content (p < 0.05). Even though both additives improved the bacterial community structure after fermentation, KT experienced the greater enhancement. At a phylum and genus level, KT had the higher relative abundance of Firmicutes and Lactobacillus, respectively. Compared with the group of 37.5% (L) moisture content, the 42.5% (M) and 47.5% moisture content (H) group increased lactic acid, acetic acid and ammonia nitrogen concentrations and reduced the pH value (p < 0.05). In conclusion, the addition of TQ and KT at the appropriate moisture content might be helpful for producing high-quality HMEC. Among the three moisture contents, 42.5% (M) moisture content provides the best silage qualities.